Solution NMR and racemic crystallography provide insights into a novel structural class of cyclic plant peptides. Issue 6 (4th October 2021) - Payne, Colton D.; Vadlamani, Grishma; Hajiaghaalipour, Fatemeh; Muhammad, Taj; Fisher, Mark F.; Andersson, Håkan S.; Göransson, Ulf; Clark, Richard J.; Bond, Charles S.; Mylne, Joshua S.; Rosengren, K. Johan
Abstract : Larger members of the PawS-Derived family of cyclic plant peptides form complex structures. The graphical abstract shows the racemic crystal structure of the homodimeric PDP-23 as well as the solution NMR structure of PDP-24. Abstract : Head-to-tail cyclic and disulfide-rich peptides are natural products with applications in drug design. Among these are the PawS-Derived Peptides (PDPs) produced in seeds of the daisy plant family. PDP-23 is a unique member of this class in that it is twice the typical size and adopts two β-hairpins separated by a hinge region. The β-hairpins, both stabilised by a single disulfide bond, fold together into a V-shaped tertiary structure creating a hydrophobic core. In water two PDP-23 molecules merge their hydrophobic cores to form a square prism quaternary structure. Here, we synthesised PDP-23 and its enantiomer comprising d -amino acids and achiral glycine, which allowed us to confirm these solution NMR structural data by racemic crystallography. Furthermore, we discovered the related PDP-24. NMR analysis showed that PDP-24 does not form a dimeric structure and it has poor water solubility, but in less polar solvents adopts near identical secondary and tertiary structure to PDP-23. The natural role of these peptides in plants remains enigmatic, as we did not observe any antimicrobial or insecticidal activity. However, the plasticity of these larger PDPs and their ability to change structure under different conditions make them appealing peptide drug scaffolds.